2021
DOI: 10.1038/s41565-021-00866-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology approaches for global infectious diseases

Abstract: Infectious diseases are a major driver of morbidity and mortality globally. Treatment of malaria, tuberculosis and human immunodeficiency virus infection are particularly challenging, as indicated by the ongoing transmission and high mortality associated with these diseases. The formulation of new and existing drugs in nano-sized carriers promises to overcome several challenges associated with the treatment of these diseases, including low on-target bioavailability, sub-therapeutic drug accumulation in microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
180
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(184 citation statements)
references
References 138 publications
(153 reference statements)
0
180
0
4
Order By: Relevance
“…Typically, DDSs can increase drug efficiency by (i) enhancing drug stability or solubility; (ii) improving release kinetics; (iii) performing a targeted drug delivery to a specific cell, tissue or molecule; (iv) allowing a higher drug penetration; or (v) obtaining better biodistribution. Moreover, it has been observed that nanocarriers can enhance drug accumulation near infections because blood vessels at infection sites are leaky [ 28 ]. Improving such relevant pharmacokinetics and pharmacodynamics factors can contribute to the reposition of antibiotics that nowadays are ineffective against resistant bacteria.…”
Section: New Strategies To Overcome Antimicrobial Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, DDSs can increase drug efficiency by (i) enhancing drug stability or solubility; (ii) improving release kinetics; (iii) performing a targeted drug delivery to a specific cell, tissue or molecule; (iv) allowing a higher drug penetration; or (v) obtaining better biodistribution. Moreover, it has been observed that nanocarriers can enhance drug accumulation near infections because blood vessels at infection sites are leaky [ 28 ]. Improving such relevant pharmacokinetics and pharmacodynamics factors can contribute to the reposition of antibiotics that nowadays are ineffective against resistant bacteria.…”
Section: New Strategies To Overcome Antimicrobial Resistance Mechanismsmentioning
confidence: 99%
“…As mentioned in Section 2.4 , bacteria can express antibiotic modifying enzymes to inactivate antibiotics and acquire resistance. Nanocarriers can reduce this inactivation by protecting antibiotics from enzymatic activity, thus, avoiding this resistance mechanism ( Figure 4 ) [ 28 ].…”
Section: Solid Lipid Nanoparticles Can Reduce Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…Stimuli-responsive nanoplatforms have unique advantages in spatial and temporal manipulations of drug release and elongation of blood retention, which provide a promising strategy for drug delivery ( 70 ). Currently, regarding unique microenvironment of bacterial infections, various responsive strategies have been widely developed on the basis of pH, enzymes, and redox gradients to improve the efficiency of antibacterial PDT.…”
Section: Unique Microenvironment In Bacterial Infection Tissuesmentioning
confidence: 99%
“…Organic nanocarrier systems have been evaluated for the treatment of local infections of the female reproductive tract, lungs and skin. Injectable nanocarriers have also been explored for the systemic delivery of drugs [ 120 ]. Regarding the types of pathogens targeted, nanoparticles have also been extensively explored for treating fungal [ 121 ], bacterial [ 120 ] and viral infections, including by Candida albicans and severe acute respiratory syndrome 2 (SARS-CoV-2) [ 122 ].…”
Section: Emergent Roles For Nanotechnology In Infectious Diseasesmentioning
confidence: 99%